2024
DOI: 10.1080/13814788.2023.2296571
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of transgender and nonbinary adults in primary care: A systematic review

Daisy Holland,
Luka C. J. White,
Marija Pantelic
et al.

Abstract: Background Transgender and nonbinary (TNB) people face barriers to primary care, which remains the main entry point for accessing gender-affirming healthcare in the UK. Objectives This systematic review aims to summarise the evidence regarding TNB people’s experiences of primary care to inform improvements in service and patient outcomes. Methods This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Indeed, across diverse disciplines, educational programs at all stages, spanning undergraduate, graduate, residency, and continuing education levels, have typically disregarded cultural or clinical training pertaining to TGD individuals ( 1 , 10 ). Various international studies, mainly conducted in the US, Canada, and Europe, have reported instances of TGD individuals feeling estranged in healthcare settings due to a lack of knowledge among HCPs ( 8 , 9 , 11 – 15 ). Consequently, TGD individuals often avoid seeking healthcare, resulting in negative consequences like poor adherence to cancer screening, delayed disease diagnosis, and self-medication without proper supervision ( 6 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, across diverse disciplines, educational programs at all stages, spanning undergraduate, graduate, residency, and continuing education levels, have typically disregarded cultural or clinical training pertaining to TGD individuals ( 1 , 10 ). Various international studies, mainly conducted in the US, Canada, and Europe, have reported instances of TGD individuals feeling estranged in healthcare settings due to a lack of knowledge among HCPs ( 8 , 9 , 11 – 15 ). Consequently, TGD individuals often avoid seeking healthcare, resulting in negative consequences like poor adherence to cancer screening, delayed disease diagnosis, and self-medication without proper supervision ( 6 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review by Holland et al [37] showed how trans adults have very disparate experiences with primary care and emphasizes the need for clinicians and policymakers to focus on the voices of the trans community when designing and improving services.…”
Section: Introductionmentioning
confidence: 99%